The Influence of Digital Marketing on Marketing Performance Mediated by Entrepreneurial Orientation in UC Makassar Student Business(i). - Elza Alvin; Jason Tandoko; Marco Panjiwinata; Cipta C. Perdana (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
The purpose of this study is to find out the Effect of Digital Marketing on Marketing Performance meidated by Entrepreneurship Orientation on Business Students (i) UC Makassar. This study uses quantitative methods and obtained a total of 52 respondents from UC Makassar students and owns a business. The analytical technique that we use in this study uses the partial least squares analysis technique with the help of Smart PLS 3.0 software. The results of the study indicate that the digital marketing variable has a positive and significant effect on entrepreneurial orientation . Furthermore, digital marketing also has a positive and significant effect on marketing performance . Then entrepreneurial orientation has a positive and significant effect on marketing performance